Accounting Conservatism and Managerial Incentives - Kwon, Young K. (Management Science, 2005)
There are two sources of agency costs under moral hazard: (1) distortions in incentive contracts and (2) implementation of suboptimal decisions. In the accounting literature, the relation between conservative accounting and agency costs of type (1) has received considerable attention (cf. Watts 2002). However, little appears to be known about the effects of accounting conservatism on agency costs of type (2) or trade-offs between agency costs of types (1) and (2). The purpose of this study is to examine this void. In a principal-agent setting in which the principal motivates the agent to expend effort using accounting earnings, this study shows that accounting earnings become more useful for reducing agency costs of type (2) when measured conservatively than when measured aggressively. Combined with the result in Kwon et al. (2001) that agency costs of type (1) decrease with accounting conservatism, this analysis suggests that conservative accounting enhances the incentive value of accounting signals with respect to both types of agency costs.